Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/cid/cix794
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Reported Penicillin Allergy on Surgical Site Infection Risk

Abstract: Patients with a reported penicillin allergy had a 50% increased odds of SSI, attributable to the receipt of second-line perioperative antibiotics. Clarification of penicillin allergies as part of routine preoperative care may decrease SSI risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
202
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(224 citation statements)
references
References 64 publications
7
202
1
4
Order By: Relevance
“…Patients with penicillin allergy labels have been shown to have an increased mortality risk from coexisting hematologic malignancies and infections from penicillin susceptible organisms such as methicillin‐susceptible Staphylococcus aureus (MSSA) . Blumenthal et al have identified that penicillin allergy labels put patients at greater risk of postoperative surgical site infections, mediated by use of alternative antibiotics. Preoperative evaluation of penicillin allergy leads to increased utilization of appropriate antimicrobials, theoretically lowering surgical site infection risk .…”
Section: Important Negative Consequences Of Penicillin Allergy Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with penicillin allergy labels have been shown to have an increased mortality risk from coexisting hematologic malignancies and infections from penicillin susceptible organisms such as methicillin‐susceptible Staphylococcus aureus (MSSA) . Blumenthal et al have identified that penicillin allergy labels put patients at greater risk of postoperative surgical site infections, mediated by use of alternative antibiotics. Preoperative evaluation of penicillin allergy leads to increased utilization of appropriate antimicrobials, theoretically lowering surgical site infection risk .…”
Section: Important Negative Consequences Of Penicillin Allergy Labelsmentioning
confidence: 99%
“…A retrospective study from a Canadian tertiary center by Picard et al demonstrated greater expenditures per penicillin allergy patient during a one‐year period due to the use of non–beta‐lactam antibiotics. Prolongations of hospitalizations, surgical site infections, and treatment failures are costly outcomes that are increased in the context of a penicillin allergy label. Huang et al report that patients with penicillin allergy labels and hematologic malignancies incur around $50,000 USD in additional costs during their hospitalizations …”
Section: Important Negative Consequences Of Penicillin Allergy Labelsmentioning
confidence: 99%
“…Unfortunately, inaccurate or unconfirmed penicillin or B‐lactam allergy and misconceptions surrounding cephalosporin cross‐reactivity mean that many patients do not receive optimum prophylaxis, or it is avoided . In one adult study, patients with a penicillin allergy label had a 50% increased risk of SSI attributed to using the recommended penicillin alternative antibiotics . However, it is known that many of these patients are falsely labeled.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alternative drugs (clindamycin, vancomycin, gentamycin) in patients reporting penicillin allergy can result in increased SSIs because concentration‐response relationships or dosing are less well defined than for penicillin. Adult patients with a reported penicillin allergy had a 50% increased odds of SSI, attributable to the receipt of second‐line perioperative antibiotics …”
Section: Perioperative Antibiotic Prophylaxismentioning
confidence: 99%